Parametric study on prestressed skewed box-girder bridge - Preeti Agarwal; Deepak Kumar Singh (Advances in Bridge Engineering, 2023)
Abstract This study employs the finite element-based CSiBridge v.20.0.0 software to examine the response of a single-cell prestressed box-girder bridge subjected to Indian loading conditions. The analyses is carried out on a simply supported bridge considering the specifications of Indian Road Congress (IRC) 6:2017, IRC 18:2000 and IRC 21:2000. An existing model of prestressed skewed bridge is validated with the published one. A convergence study is conducted for determining the model’s mesh size. An extensive parametric study is carried out to gain a better understanding of the response of a skewed prestressed bridge. The parameters variables are: Skew angle (0°, 10°, 20°, 30°, 40°, 50°, and 60°); Span (35, 40, 45, 50, 55, and 60 m); and Span-depth ratio (10, 12, 14, 16 and 18). The results of this study are presented as ratios of Bending moment, Shear force, Torsional moment, and Vertical deflection. Finally, equations for estimation of these ratios for different span and span-depth ratio are also deduced from the statistical approach so that the results of skewed bridges may be evaluated directly. It is determined that the skewed bridge outperforms the straight bridge because of its higher span-depth ratio, which results in less bending moment development. Evidence suggests that the skewness may help to lessen the prestress load’s dominance. The findings of this study may be helpful to engineers and designers in the analysis and design of prestresssed skewed box-girder bridges.